BLOCKCHAIN TECHNOLOGY IN THE CARBON MARKET: ENHANCING TRANSPARENCY AND TRUST IN EMISSIONS TRADING - Prawitasari, Putu Putri; Nurmalasari, Made Ratih; Kumalasari, Putu Diah (LPPM Universitas Bina Bangsa, 2025)
Climate change demands urgent solutions, and blockchain technology offers a promising way to enhance transparency and trust in emissions trading, a key component of carbon markets. By providing a decentralized, secure platform for tracking and verifying emissions data, blockchain can address issues like lack of transparency and trust that have limited the effectiveness of carbon markets. This innovation could streamline the trading of carbon credits, promoting sustainable practices among businesses and supporting the transition to a low-carbon economy. The study employs qualitative research methods, including a literature review from the Scopus database and case study analysis, to explore the application of blockchain in carbon markets. Industry reports and real-world case studies provide additional insights. Findings suggest that while blockchain has significant potential, its successful integration into the carbon market requires overcoming several barriers, including regulatory, technological, and organizational challenges. The paper highlights both the opportunities and obstacles for blockchain's adoption in carbon trading, contributing to efforts aimed at mitigating climate change.